A retrospective study: root cause analysis of reported serious adverse event and development of corrective action and preventive action for deviated serious adverse event reports at a clinical trial site management office - Raddi, Dayanand; Deveriniti, Revena S.; Ganachari, M. S.; Salimath, Geetanjali (International Journal of Clinical Trials, 2020)
Background: Serious adverse events (SAEs) are preventable if reported on time. Assessment of harm caused by clinical trials is difficult than assessing the benefits as it relied on the information as recorded by the study team. Hence it is important to have knowledge about quality safety reporting. The objectives of the study were to assess root cause for the timeline deviation found in SAE report and to develop the corrective action and preventive action to minimize deviation rate. Methods: A retrospective study was conducted in KLE’s Hospital and MRC, Belagavi. Data was collected from SAE documented trial study files. Between August 2016 to August 2019, 25 SAE occurred during clinical trials which were included in the study through complete enumeration and purposive sampling. Results: Data was analyzed for SAE reporting timeline where in no deviation was found in initial report. It was seen that all SAEs were not related to investigational product. The narrations of SAE were according to standardized format as per Ethics Committee review report. A gap was observed between onset of SAE and initial report in 16 case reports. Conclusions: The study concluded that there was a lag in reporting from onset of SAE to initial report even though there was no deviation observed in the initial report timeline. The main contributing factors were admitting in different hospital without information and lack of knowledge by subjects or their relatives which shows the need of awareness about quality safety reporting.